Genetic Variability of Eggplant (Solanum Melongena L. 'Nasubi') Based on ISSR Markers and Phenotypic Characters - Nabila Shafura; Annas Rabbani; Budi Setiadi Daryono (Journal of Biodiversity and Biotechnology, 2022)
‘Nasubi’ eggplant seeds have occurred since 2018. In addition, plants that produce fruit phenotypic characters differ from those planted before the planting period in 2018. These three factors cause the decline in harvest rates and the current high increase in production costs. Observation of variations in phenotypic and molecular characters with ISSR molecular markers between seeds before 2018 and after 2018, became the first step for the research team to reveal information on the uniformity of phenotypic and molecular characters in eggplant ‘Nasubi’ from seeds purchased by farmers before 2018 and post-2018. The results of the molecular analysis with ISSR primary molecular markers namely UBC 809, UBC 815, IBC 880, UBC 888, and UBC 892, showed that the six samples had a high similarity index of 90% and resulted in a low polymorphism average of 12%. The results of the phenotypic analysis showed that eggplants from the seeds before 2018 and seeds after 2018 in this study had variations in the character of the leaf tip angle, leaf base, flower crown color, stamen color, young fruit color, fruit curve, and fruit tip shape.